"They Said the Course Would Be Wasted On Me Because I Was A Girl": Mothers, Daughters, And Shifting Forms Of Female Activism in the Ukrainian Left in Twentieth-Century Canada - Hinther, Rhonda L. (Atlantis, 2007)
A generation divided progressive Ukrainian mothers and daughters. Nonetheless, they shared cultural and political lessons learned at the Ukrainian labour temples, in their neighbourhoods, and on picket lines. They absorbed, transformed and put these ideas to work in a variety of ways to build, challenge, change, or leave the Ukrainian left.